Type a math problem

This site uses cookies for analytics, personalized content and ads. By continuing to browse this site, you agree to this use. Learn more

Type a math problem

Evaluate

\frac{1}{2}=0.5

$21 =0.5$

Solution Steps

\sqrt { \frac { 5 } { 20 } }

$205 $

Reduce the fraction \frac{5}{20}=0.25 to lowest terms by extracting and canceling out 5.

Reduce the fraction $205 =0.25$ to lowest terms by extracting and canceling out $5$.

\sqrt{\frac{1}{4}}=0.5

$41 =0.5$

Rewrite the square root of the division \frac{1}{4}=0.25 as the division of square roots \frac{\sqrt{1}}{\sqrt{4}}=0.5. Take the square root of both numerator and denominator.

Rewrite the square root of the division $41 =0.25$ as the division of square roots $4 1 =0.5$. Take the square root of both numerator and denominator.

\frac{1}{2}=0.5

$21 =0.5$

Giving is as easy as 1, 2, 3

Get 1,000 points to donate to a school of your choice when you join Give With Bing

Share

Copy

Copied to clipboard

\sqrt{\frac{1}{4}}=0.5

Reduce the fraction \frac{5}{20}=0.25 to lowest terms by extracting and canceling out 5.

\frac{1}{2}=0.5

Rewrite the square root of the division \frac{1}{4}=0.25 as the division of square roots \frac{\sqrt{1}}{\sqrt{4}}=0.5. Take the square root of both numerator and denominator.

Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

$x_{2}−4x−5=0$

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

$4sinθcosθ=2sinθ$

Linear equation

y = 3x + 4

$y=3x+4$

Arithmetic

699 * 533

$699∗533$

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { - 1 } & { 1 } & { 5 } \end{array} \right]

$[25 34 ][2−1 01 35 ]$

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

${8x+2y=467x+3y=47 $

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

$dxd (x−5)(3x_{2}−2) $

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

$∫_{0}xe_{−x_{2}}dx$

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}

$x→−3lim x_{2}+2x−3x_{2}−9 $

Back to top